Enhanced aluminum oxide ceramic substrate and preparation method thereof

By using modified alumina, magnesium oxide and yttrium dioxide, the density and mechanical properties of alumina ceramic substrates are improved, and the problems of low bending strength and electrical breakdown resistance of existing ceramic substrates are solved, thereby achieving higher mechanical strength and longer service life.

CN119504236APending Publication Date: 2025-02-25SUZHOU JINGCI SUPER HARD MATERIALS

Patent Information

Application Number
CN202411512251.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing alumina ceramic substrates have low bending strength and electrical breakdown resistance, which are prone to damage during use, resulting in a reduced service life.

Method used

The density and mechanical properties of the ceramic substrate are improved by using modified alumina, magnesium oxide and yttrium dioxide.

Benefits of technology

It significantly improves the mechanical strength, hardness, electrical insulation properties and thermal conductivity of the alumina ceramic substrate, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105771270000081
    Figure BDA0005105771270000081
  • Figure BDA0005105771270000091
    Figure BDA0005105771270000091
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic preparation, and particularly discloses an enhanced aluminum oxide ceramic substrate and a preparation method thereof. The enhanced aluminum oxide ceramic substrate is prepared from the following raw materials in percentage by weight: 0.005 to 0.01 percent of magnesium oxide, 0.020 to 0.025 percent of yttrium oxide, 65 to 70 percent of solvent, 1.5 to 2.5 percent of dispersing agent, 4 to 6 percent of plasticizer, 5 to 7 percent of binder and 0.7 to 0.9 percent of surfactant which are added on the basis of the weight of the modified aluminum oxide. The enhanced aluminum oxide ceramic substrate prepared by the preparation method has excellent electrical insulation performance and relatively high thermal conductivity, chemical stability and mechanical strength, and the obtained aluminum oxide ceramic substrate has relatively good density, mechanical property and thermal stability by mixing various raw material components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic preparation, and more specifically, to an enhanced alumina ceramic substrate and a preparation method thereof. Background Art

[0002] Alumina ceramic substrate is a ceramic material made of high-purity alumina as the main raw material. It has excellent thermal, mechanical, chemical and dielectric properties and is widely used in electronics, microelectronics, semiconductors, optics, machinery, chemical industry, aerospace and other fields, such as integrated circuit packaging, LED packaging, microwave devices, high temperature sensors, chemical reactors, optical windows, etc.

[0003] An important molding method for preparing alumina ceramic substrates usually adopts the tape casting molding process. The tape casting molding process includes slurry preparation, molding, drying and other processes. It is necessary to add solvents, binders, dispersants, plasticizers and defoaming agents to the ceramic powder to prepare a stable and uniform slurry. The slurry is formed by a tape casting machine to obtain a tape casting raw tape of a certain thickness. After the raw tape is dried and sintered, the desired ceramic substrate is obtained.

[0004] However, the existing alumina ceramic substrate has the disadvantages of low bending strength and low electrical breakdown strength, and is easily damaged during use, which seriously reduces the service life of the alumina ceramic substrate. Summary of the invention

[0005] In order to improve the problem of low mechanical strength of alumina ceramic substrates, the present application provides a reinforced alumina ceramic substrate and a preparation method thereof.

[0006] In a first aspect, the present application provides an enhanced alumina ceramic substrate, which adopts the following technical solution: A reinforced alumina ceramic substrate comprises the following raw materials: modified alumina, 0.005-0.01% of magnesium oxide, 0.020-0.025% of yttrium trioxide, 65-70% of solvent, 1.5-2.5% of dispersant, 4-6% of plasticizer, 5-7% of binder and 0.7-0.9% of surfactant added in percentage by weight based on the weight of the modified alumina.

[0007] By adopting the above technical scheme, the modified alumina as the alumina ceramic substrate has excellent electrical insulation properties, high thermal conductivity, chemical stability, mechanical strength and hardness. Magnesium oxide and yttrium trioxide are used as sintering aids to reduce the sintering temperature of the alumina ceramic substrate and promote the bonding between particles, thereby improving the density and mechanical properties of the ceramic substrate. The addition of magnesium oxide and yttrium trioxide can further improve the electrical insulation properties and thermal conductivity of the alumina ceramic substrate, enhance the chemical stability, hardness and bending strength of the alumina ceramic substrate, and enhance its mechanical properties. It can also optimize the microstructure of the alumina ceramic substrate, promote grain refinement, and improve the uniformity and density of the material.

[0008] In the slurry stage of preparing alumina ceramic substrates, solvents are used to dissolve or disperse binders, dispersants, plasticizers, surfactants and modified alumina to form a uniform and stable slurry. Dispersants can effectively prevent modified alumina from agglomerating in the slurry, ensure that the particles are evenly dispersed, ensure that the slurry remains uniform for a long time, form a uniform microstructure and improve the comprehensive performance of the ceramic substrate. Plasticizers can increase the plasticity of the slurry, making it easier to shape during the molding process, reducing cracks and deformation, and improving the precision and consistency of molding; in addition, plasticizers can control the shrinkage of the green body during the drying process, reduce deformation and cracks caused by uneven drying, and improve the uniformity and density of the green body.

[0009] The binder plays a role in connecting the modified alumina particles in the slurry, which helps to improve the stability of the slurry and ensure that the particles can remain tightly bound during the drying and sintering process to form a dense ceramic substrate. The surfactant can significantly reduce the surface tension of the slurry, help improve the fluidity and dispersibility of the slurry, and ensure that the alumina particles are evenly distributed in the slurry. During the slurry preparation and molding process, the surfactant can control the formation of bubbles, reduce pores and defects, and improve the density and surface quality of the ceramic substrate. The various raw material components are mixed to obtain an alumina ceramic substrate with good density, mechanical properties and thermal stability.

[0010] Optionally, the dispersant is prepared by mixing polyacrylic acid, castor oil and sodium polyacrylate in a mass ratio of 1:0.5-0.6:0.7-0.9.

[0011] By adopting the above technical scheme, polyacrylic acid and sodium polyacrylate can be adsorbed on the surface of alumina particles, and the agglomeration between particles is prevented by electrostatic repulsion and steric hindrance effect, thereby ensuring that the alumina particles are evenly dispersed in the slurry; castor oil reduces the mutual attraction between alumina particles through the characteristics of its molecular structure, prevents the alumina particles from agglomerating in the slurry, and ensures that the particles are evenly dispersed. At the same time, castor oil has good lubricating properties, which can reduce the friction between particles and help improve the fluidity and formability of the slurry. At the same time, during the sintering process, its decomposition products can play a certain lubricating role, reduce the shrinkage stress of the green body, and improve the uniformity and density of the green body.

[0012] Polyacrylic acid and sodium polyacrylate have good thickening properties, and castor oil has good emulsifying properties. After mixing polyacrylic acid, castor oil and sodium polyacrylate, a stable emulsion can be formed to improve the dispersibility and emulsification stability of the system. Polyacrylic acid, castor oil and sodium polyacrylate work together on the particle surface to effectively prevent agglomeration between particles, ensure that the particles are evenly dispersed in the slurry, and significantly improve the dispersion effect of the slurry.

[0013] Optionally, the plasticizer is prepared by mixing butyl benzyl phthalate, polyethylene glycol and paraffin in a mass ratio of 1:2-3:0.6-0.8.

[0014] By adopting the above technical scheme, butyl benzyl phthalate, polyethylene glycol and paraffin can respectively reduce the viscosity of the slurry and improve its plasticity, so that the slurry can better maintain its shape during the molding process, reduce the risk of cracking and deformation, and improve the dimensional accuracy and surface quality of the ceramic substrate; butyl benzyl phthalate, polyethylene glycol and paraffin are mixed to form a stable suspension, which further reduces the viscosity of the slurry and improves the rheological properties of the slurry, making it easier to flow and mold during the molding process, while reducing the formation of bubbles and improving the density and uniformity of the ceramic substrate.

[0015] Optionally, the adhesive is prepared by mixing modified hydroxyethyl cellulose, pineol and epoxy resin in a mass ratio of 1:1.5-2:0.7-0.9.

[0016] By adopting the above technical scheme, modified hydroxyethyl cellulose and terpineol can interact with the hydroxyl groups on the surface of alumina particles through hydrogen bonds and van der Waals forces, thereby enhancing the binding force between particles, improving the stability of the slurry, and preventing the particles from settling; the epoxy resin forms a continuous bonding phase after curing, firmly bonding the alumina particles together, and improving the mechanical strength and toughness of the ceramic substrate. The modified hydroxyethyl cellulose, terpineol and epoxy resin are uniformly mixed to form a stable slurry, improve the rheological properties of the slurry, improve the stability of the slurry, prevent the particles from settling during long-term standing, and maintain the uniformity and stability of the slurry.

[0017] Optionally, the preparation method of the modified alumina comprises the following steps: calcining the alumina at 300-350°C for 3-4h, dispersing the alumina in a dimethyl sulfoxide solution, ultrasonicating for 30-35min, adding graphene and polyurethane, stirring at 80-85°C for 1-2h, drying, and grinding to obtain modified alumina.

[0018] By adopting the above technical scheme, during the calcination process of alumina, moisture, organic matter and other volatile impurities in alumina will be removed, thereby improving the purity of alumina, and changing the particle size, specific surface area and porosity of alumina, so that it has better fluidity, compactness and chemical stability, which is helpful for the subsequent preparation of enhanced alumina ceramic substrates.

[0019] Dimethyl sulfoxide has good solubility and chemical stability, and can effectively disperse graphene sheets to prevent them from agglomerating. Graphene can be loaded on the surface of alumina. Polyurethane has viscosity, which allows graphene to stably adhere to the surface of alumina, making the modified alumina have better comprehensive properties.

[0020] Graphene has extremely high strength and elastic modulus, and can improve the mechanical properties of alumina ceramic substrates, such as bending strength and fracture toughness. Moreover, the addition of graphene can effectively disperse stress and inhibit crack propagation, thereby enhancing the crack resistance and wear resistance of the ceramic substrate.

[0021] In addition, the addition of graphene can promote the sintering process of alumina ceramic substrates, reduce the sintering temperature, shorten the sintering time, and improve production efficiency; the dense structure of graphene can serve as a protective layer for alumina ceramic substrates, improve their corrosion resistance in harsh environments, and extend the service life of alumina materials.

[0022] Optionally, the mass ratio of the aluminum oxide, graphene and polyurethane is 1:0.03-0.05:0.1-0.2.

[0023] By adopting the above technical solution, the mass ratio of aluminum oxide, graphene and polyurethane is further limited within a certain range, thereby improving the mechanical properties of modified aluminum oxide. Graphene has extremely high strength and elastic modulus. Graphene is loaded on the surface of aluminum oxide, thereby improving the mechanical properties of aluminum oxide such as bending strength and fracture toughness. Polyurethane has viscosity, thereby allowing graphene to stably adhere to the surface of aluminum oxide, thereby making the modified aluminum oxide have better comprehensive properties. Aluminum oxide, graphene and polyurethane have a synergistic effect and cooperate with each other to improve the comprehensive properties of aluminum oxide such as mechanical properties and corrosion resistance.

[0024] Optionally, the preparation method of the modified hydroxyethyl cellulose comprises the following steps: dispersing hydroxyethyl cellulose in deionized water, stirring at a temperature of 60-65° C. for 8-12 minutes, adding nano-silicon dioxide and a silane coupling agent, stirring evenly, ultrasonically degassing, drying, and grinding to obtain modified hydroxyethyl cellulose.

[0025] By adopting the above technical solution, nano-silica can subsequently improve the mechanical properties, thermal stability and corrosion resistance of the alumina ceramic substrate, such as bending strength and fracture toughness, and help form a denser structure inside the alumina material, reduce pores and defects, and thus enhance the strength and toughness of the alumina material.

[0026] Nano-silica is dispersed in the aqueous solution of hydroxyethyl cellulose. The alkyl coupling agent can serve as a bridge between hydroxyethyl cellulose and nano-silica, improving the interfacial bonding force between nano-silica and hydroxyethyl cellulose through chemical bonding, which helps to improve the subsequent mechanical properties of alumina materials such as tensile strength, flexural strength and fracture toughness.

[0027] The modified hydroxyethyl cellulose not only has good viscosity and thickening properties, but also has excellent mechanical properties. It is subsequently used in alumina materials to improve the mechanical properties of alumina materials such as tensile strength, flexural strength and fracture toughness, and also makes the ceramic substrate structure dense, ensuring that the particles can remain tightly combined during the drying and sintering process to form a dense ceramic substrate.

[0028] Optionally, the mass ratio of the hydroxyethyl cellulose, nano-silicon dioxide and silane coupling agent is 1:0.4-0.6:0.2-0.3.

[0029] By adopting the above technical scheme, the mass ratio of hydroxyethyl cellulose, nano silicon dioxide and silane coupling agent is further limited to significantly improve the viscosity and mechanical properties of hydroxyethyl cellulose within a certain range. Silane coupling agent, as a bridge between hydroxyethyl cellulose and nano silicon dioxide, improves the interfacial bonding force between them through chemical bonding, thereby improving the mechanical properties of the system, such as tensile strength, flexural strength and fracture toughness. In addition, the addition of nano silicon dioxide can improve the dispersibility of hydroxyethyl cellulose in the material and avoid agglomeration, while the silane coupling agent further enhances this dispersibility and ensures the uniformity and stability of the material.

[0030] In a second aspect, the present application provides a method for preparing an enhanced alumina ceramic substrate, comprising the following steps: (1) vacuum drying the modified alumina, magnesium oxide and yttrium trioxide respectively; the drying condition is drying at 75-80° C. for 10-12 hours; (2) ball-milling the solvent, dispersant, plasticizer, binder and surfactant to obtain a mixed solution, and controlling the pH value of the mixed solution to 8-9 by adding ammonia water; (3) adding the powder obtained by drying in step (1) to the mixed solution obtained in step (2), and continuing ball milling for 30-32 hours; (4) Casting is performed, and drying is performed at 95-100° C. for 3-4 hours to prepare an alumina ceramic green body, and the temperature is raised to 1600-1650° C. and sintered for 5-6 hours to obtain an enhanced alumina ceramic substrate.

[0031] By adopting the above technical scheme and the above preparation method, the obtained alumina ceramic substrate has the advantages of high purity, density and strong mechanical properties, so that it has broad application prospects in electronics, microelectronics, semiconductors, optics, machinery, chemical industry, aerospace and other fields.

[0032] Optionally, in step (3), the ball milling speed is 300-400 r / min, and the ball milling time is 4-5 h.

[0033] By adopting the above technical solution, the rotation speed and milling time of the ball mill are further limited, so that the alumina raw material powder is further refined, the particle size is reduced, and the specific surface area of ​​the powder is increased. The fine particles help to increase the density in the subsequent molding and sintering processes, thereby improving the performance of the ceramic substrate.

[0034] In summary, this application has the following beneficial effects: 1. In this application, the modified alumina as an alumina ceramic substrate has excellent electrical insulation properties, high thermal conductivity, chemical stability, mechanical strength and hardness. Magnesium oxide and yttrium trioxide are used as sintering aids to reduce the sintering temperature of the alumina ceramic substrate and promote the bonding between particles, thereby improving the density and mechanical properties of the ceramic substrate.

[0035] 2. The addition of magnesium oxide and yttrium trioxide in the present application can further improve the electrical insulation performance and thermal conductivity of the alumina ceramic substrate, enhance the chemical stability, hardness and bending strength of the alumina ceramic substrate, and enhance its mechanical properties.

[0036] 3. In the present application, the binder plays the role of connecting the modified alumina particles in the slurry, which helps to improve the stability of the slurry and ensure that the particles can remain tightly combined during the drying and sintering process to form a dense ceramic substrate. DETAILED DESCRIPTION

[0037] Preparation example of modified alumina Preparation Example 1-1 The preparation method of modified alumina comprises the following steps: calcining 100 g of alumina at 350° C. for 4 h, dispersing the alumina in 200 mL of dimethyl sulfoxide solution, ultrasonicating the alumina for 35 min, adding graphene and polyurethane, stirring the alumina at 85° C. for 2 h, drying, and grinding to obtain modified alumina.

[0038] The mass ratio of alumina, graphene and polyurethane is 1:0.03:0.2.

[0039] Preparation Example 1-2 The difference from Preparation Example 1-1 is that calcination was not performed.

[0040] Preparation Example 1-3 The difference from Preparation Example 1-1 is that graphene is not added.

[0041] Preparation Example 1-4 The difference from Preparation Example 1-1 is that no polyurethane is added.

[0042] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of aluminum oxide, graphene and polyurethane is 1:0.05:0.1.

[0043] Preparation Example 1-6 The difference from Preparation Example 1-1 is that the mass ratio of aluminum oxide, graphene and polyurethane is 1:0.01:0.4.

[0044] Preparation Example of Modified Hydroxyethyl Cellulose Preparation Example 2-1 The preparation method of modified hydroxyethyl cellulose comprises the following steps: dispersing 50g of hydroxyethyl cellulose in 70mL of deionized water, stirring at a temperature of 65°C for 12min, adding nano-silicon dioxide and a silane coupling agent, stirring evenly, ultrasonically degassing for 5-6h, drying, and grinding to obtain modified hydroxyethyl cellulose.

[0045] The mass ratio of hydroxyethyl cellulose, nano-silica and silane coupling agent is 1:0.4:0.2.

[0046] Preparation Example 2-2 The difference from Preparation Example 2-1 is that no nano-silicon dioxide is added.

[0047] Preparation Example 2-3 The difference from Preparation Example 2-1 is that no silane coupling agent is added.

[0048] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of hydroxyethyl cellulose, nano-silica and silane coupling agent is 1:0.6:0.3.

[0049] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of hydroxyethyl cellulose, nano-silica and silane coupling agent is 1:0.1:0.6. Example

[0050] Example 1 A reinforced alumina ceramic substrate comprises the following raw materials: 200g of modified alumina, 0.005% of magnesium oxide, 0.025% of yttrium trioxide, 65% of solvent, 1.5% of dispersant, 4% of plasticizer, 7% of binder and 0.7% of surfactant added in percentage by weight based on the weight of the modified alumina.

[0051] The solvent is a mixture of water, isopropanol and ethanol in a mass ratio of 1:0.7:0.8; The particle size of aluminum oxide is 0.75 μm; the particle size of magnesium oxide is 20 nm; and the particle size of yttrium oxide is 50 nm.

[0052] The dispersant is prepared by mixing polyacrylic acid, castor oil and sodium polyacrylate in a mass ratio of 1:0.5:0.7.

[0053] The plasticizer is prepared by mixing butyl benzyl phthalate, polyethylene glycol and paraffin in a mass ratio of 1:2:0.6.

[0054] The adhesive is prepared by mixing modified hydroxyethyl cellulose, pine alcohol and epoxy resin in a mass ratio of 1:2:0.7, and the surfactant is non-ionic octylphenoxyethanol.

[0055] The method for preparing the enhanced alumina ceramic substrate comprises the following steps: (1) vacuum drying the modified alumina, magnesium oxide and yttrium trioxide respectively; the drying condition is drying at 75° C. for 12 h; (2) adding a solvent, a dispersant, a plasticizer, a binder and a surfactant into a ball mill to obtain a mixed solution, and controlling the pH value of the mixed solution to 8 by adding ammonia water; (3) adding the powder obtained by drying in step (1) to the mixed solution obtained in step (2), and continuing ball milling for 30 hours; (4) The film was cast on a large-scale casting machine, dried at 100°C for 3 hours to prepare an alumina ceramic green body, and then heated to 1600°C and sintered for 5 hours to obtain an enhanced alumina ceramic substrate.

[0056] The ball milling speed is 300r / min and the ball milling time is 4-5h.

[0057] The modified alumina was prepared according to Preparation Example 1-1, and the modified hydroxyethyl cellulose was prepared according to Preparation Example 2-1.

[0058] Example 2 A reinforced alumina ceramic substrate, which differs from Example 1 in that it includes the following raw materials: modified alumina, 0.01% of magnesium oxide, 0.020% of yttrium oxide, 70% of solvent, 2.5% of dispersant, 6% of plasticizer, 5% of binder, and 0.9% of surfactant added in percentage by weight based on the weight of the modified alumina.

[0059] The dispersant is prepared by mixing polyacrylic acid, castor oil and sodium polyacrylate in a mass ratio of 1:0.6:0.9.

[0060] The plasticizer is prepared by mixing butyl benzyl phthalate, polyethylene glycol and paraffin in a mass ratio of 1:3:0.8.

[0061] The adhesive is prepared by mixing modified hydroxyethyl cellulose, pineol and epoxy resin in a mass ratio of 1:1.5:0.9.

[0062] The method for preparing the enhanced alumina ceramic substrate comprises the following steps: (1) vacuum drying the modified alumina, magnesium oxide and yttrium trioxide respectively; the drying condition is drying at 80° C. for 10 h; (2) adding a solvent, a dispersant, a plasticizer, a binder and a surfactant into a ball mill and ball milling to obtain a mixed solution, and controlling the pH value of the mixed solution to 9 by adding ammonia water; (3) adding the powder obtained by drying in step (1) to the mixed solution obtained in step (2), and continuing ball milling for 32 hours; (4) The film was cast on a large-scale casting machine, dried at 95°C for 4 hours to prepare an alumina ceramic green body, and then heated to 1650°C and sintered for 6 hours to obtain an enhanced alumina ceramic substrate.

[0063] The ball milling speed was 400 r / min and the ball milling time was 5 h.

[0064] Example 3 A reinforced alumina ceramic substrate, which differs from Example 1 in that the modified alumina adopts Preparation Example 1-2.

[0065] Example 4 A reinforced alumina ceramic substrate, which differs from Example 1 in that the modified alumina adopts Preparation Example 1-3.

[0066] Example 5 A reinforced alumina ceramic substrate, which differs from Example 1 in that the modified alumina is prepared according to Preparation Examples 1-4.

[0067] Example 6 A reinforced alumina ceramic substrate, which differs from Example 1 in that the modified alumina is prepared according to Preparation Examples 1-5.

[0068] Example 7 A reinforced alumina ceramic substrate, which differs from Example 1 in that the modified alumina is prepared according to Preparation Examples 1-6.

[0069] Example 8 A reinforced alumina ceramic substrate, which differs from Example 1 in that the modified hydroxyethyl cellulose adopts the preparation example 2-2.

[0070] Example 9 A reinforced alumina ceramic substrate, which is different from Example 1 in that the modified hydroxyethyl cellulose adopts Preparation Example 2-3.

[0071] Example 10 A reinforced alumina ceramic substrate, which is different from Example 1 in that the modified hydroxyethyl cellulose is prepared as in Preparation Example 2-4.

[0072] Embodiment 11 A reinforced alumina ceramic substrate, which is different from Example 1 in that the modified hydroxyethyl cellulose is prepared as in Preparation Example 2-5.

[0073] Comparative Example Comparative Example 1 A reinforced alumina ceramic substrate, which differs from Example 1 in that the modified alumina is replaced by an equal amount of alumina.

[0074] Performance testing The enhanced alumina ceramic substrates prepared in Examples 1-11 and Comparative Example 1 were subjected to performance tests according to the national standard GB / T14619-2013.

[0075] Sintering density: Instrument model: MZ-A600; Bending strength: The bending strength of the material is tested on a universal testing machine using a three-point bending test method. f , sample size: l×b×h=36mm×3mm×4mm, span is 30mm, and the pressure head descent rate is 0.5mm / min.

[0076] Fracture toughness: The fracture toughness of the material was measured by the single-edge notched beam method (SENB method) using a WDW electronic universal testing machine, and the loading rate was set to 0.05 mm / min.

[0077] Breakdown strength: Laser scribed Φ35mm wafers, silver-plated on both sides, thickness 1.5±0.5mm, breakdown strength was tested using a voltage breakdown tester. The test results are shown in Table 1.

[0078] Table 1 Test data of embodiments and comparative examples Combining the examples and the data in Table 1, it can be seen that the enhanced alumina ceramic substrates prepared in Examples 1-2, Example 6 and Example 10 have good density and mechanical properties. Among them, the density of Example 1 is 3.85 g / cm 3 , the flexural strength is 412MPa, and the fracture toughness is 5.98MPa﹒ m 1 / 2 The breakdown strength is 19.9 kv / mm. This shows that the density and mechanical properties of the enhanced alumina ceramic substrate prepared in this application are good, and the alumina ceramic substrate obtained by mixing various raw material components has good density, mechanical properties and thermal stability.

[0079] In the preparation method of modified alumina in Example 3, calcination is not performed. As shown in Table 1, compared with Example 1, the density of Example 3 is 3.65 g / cm 3 , the flexural strength is 401MPa, and the fracture toughness is 5.77MPa﹒ m 1 / 2 , the breakdown strength is 19.1kv / mm. This shows that during the calcination process of alumina in the present application, moisture, organic matter and other volatile impurities in alumina will be removed, thereby improving the purity of alumina, and changing the particle size, specific surface area and porosity of alumina, making it have better fluidity, compactness, chemical stability and adsorption, which is helpful for the subsequent preparation of enhanced alumina ceramic substrates.

[0080] In the preparation method of modified alumina in Example 4, graphene is not added. As shown in Table 1, compared with Example 1, the density of Example 4 is 3.40 g / cm 3 , flexural strength is 385MPa, fracture toughness is 5.50MPa﹒ m 1 / 2 , the breakdown strength is 17.7kv / mm. This shows that the graphene in the present application has extremely high strength and elastic modulus, and improves the mechanical properties of the substrate such as bending strength and fracture toughness in the alumina ceramic substrate. Moreover, the addition of graphene can effectively disperse stress and inhibit the expansion of cracks, thereby enhancing the crack resistance and wear resistance of the ceramic substrate.

[0081] In the preparation method of modified alumina in Example 5, polyurethane is not added. As shown in Table 1, compared with Example 1, the density of Example 5 is 3.51 g / cm 3 , the flexural strength is 390MPa, and the fracture toughness is 5.61MPa﹒ m 1 / 2 The breakdown strength is 18.3 kv / mm. This indicates that the polyurethane of the present application has viscosity, which allows graphene to stably adhere to the surface of alumina, so that the modified alumina has better comprehensive properties.

[0082] Example 7 changes the mass ratio of alumina, graphene and polyurethane. It can be seen from Table 1 that compared with Example 1, the effects of density, flexural strength, fracture toughness and breakdown strength are better than those of Examples 4-5, but worse than those of Examples 1 and 6, indicating that graphene is loaded on the surface of alumina to improve the mechanical properties of alumina such as flexural strength and fracture toughness. Polyurethane has viscosity, which makes graphene stably adhere to the surface of alumina, so that the modified alumina has better comprehensive properties. Alumina, graphene and polyurethane have a synergistic effect and cooperate with each other to improve the comprehensive properties of alumina such as mechanical properties and corrosion resistance.

[0083] In the preparation method of modified hydroxyethyl cellulose in Example 8, nano-silicon dioxide is not added. As shown in Table 1, compared with Example 1, the density of Example 8 is 3.67 g / cm 3 , the flexural strength is 403MPa, and the fracture toughness is 5.79MPa﹒ m 1 / 2 , the breakdown strength is 19.3kv / mm. This shows that the nano-silica of the present application can subsequently improve the mechanical properties such as bending strength and fracture toughness, thermal stability and corrosion resistance of the alumina ceramic substrate, help to form a denser structure inside the alumina material, reduce pores and defects, and thus enhance the strength and toughness of the alumina material.

[0084] In the preparation method of modified hydroxyethyl cellulose in Example 9, no silane coupling agent is added. As shown in Table 1, compared with Example 1, the density of Example 9 is 3.71 g / cm 3 , the flexural strength is 406MPa, and the fracture toughness is 5.83MPa﹒ m 1 / 2 , the breakdown strength is 19.4 kv / mm. This shows that the alkyl coupling agent of the present application can serve as a bridge between hydroxyethyl cellulose and nano-silica, improve the interfacial bonding force between nano-silica and hydroxyethyl cellulose through chemical bonding, and help improve the subsequent mechanical properties of alumina materials such as tensile strength, flexural strength and fracture toughness.

[0085] Example 11 changes the mass ratio of hydroxyethyl cellulose, nano-silica and silane coupling agent. As can be seen from Table 1, compared with Example 1, the effects of density, flexural strength, fracture toughness and breakdown strength are better than those of Examples 8-9, but worse than those of Examples 1 and 10, indicating that the silane coupling agent in the present application acts as a bridge between hydroxyethyl cellulose and nano-silica, improving the interfacial bonding force between them through chemical bonding, thereby improving the mechanical properties of the system, such as tensile strength, flexural strength and fracture toughness.

[0086] In Comparative Example 1, the modified alumina is replaced by an equal amount of alumina. As shown in Table 1, compared with Example 1, the density of Comparative Example 1 is 3.12 g / cm 3 , the flexural strength is 370MPa, and the fracture toughness is 4.23MPa﹒ m 1 / 2 The breakdown strength is 16.2 kv / mm. This indicates that the modified alumina of the present application as an alumina ceramic substrate has excellent chemical stability, mechanical strength and hardness, and the alumina ceramic substrate obtained by mixing the various components has good density, mechanical properties and thermal stability.

[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A reinforced alumina ceramic substrate, characterized in that: The raw materials include: modified alumina, 0.005-0.01% of magnesium oxide, 0.020-0.025% of yttrium trioxide, 65-70% of solvent, 1.5-2.5% of dispersant, 4-6% of plasticizer, 5-7% of binder and 0.7-0.9% of surfactant added in percentage by weight based on the weight of the modified alumina.

2. The enhanced alumina ceramic substrate according to claim 1, characterized in that: The dispersant is prepared by mixing polyacrylic acid, castor oil and sodium polyacrylate in a mass ratio of 1:0.5-0.6:0.7-0.

9.

3. The enhanced alumina ceramic substrate according to claim 1, characterized in that: The plasticizer is prepared by mixing butyl benzyl phthalate, polyethylene glycol and paraffin in a mass ratio of 1:2-3:0.6-0.

8.

4. The enhanced alumina ceramic substrate according to claim 1, characterized in that: The adhesive is prepared by mixing modified hydroxyethyl cellulose, pineol and epoxy resin in a mass ratio of 1:1.5-2:0.7-0.

9.

5. The enhanced alumina ceramic substrate according to claim 1, characterized in that: The preparation method of the modified alumina comprises the following steps: calcining the alumina at 300-350°C for 3-4h, dispersing the alumina in a dimethyl sulfoxide solution, ultrasonicating for 30-35min, adding graphene and polyurethane, stirring at 80-85°C for 1-2h, drying, and grinding to obtain the modified alumina.

6. The enhanced alumina ceramic substrate according to claim 5, characterized in that: The mass ratio of the aluminum oxide, graphene and polyurethane is 1:0.03-0.05:0.1-0.

2.

7. The enhanced alumina ceramic substrate according to claim 4, characterized in that: The preparation method of the modified hydroxyethyl cellulose comprises the following steps: dispersing the hydroxyethyl cellulose in deionized water, stirring at a temperature of 60-65° C. for 8-12 minutes, adding nano silicon dioxide and a silane coupling agent, stirring evenly, ultrasonically degassing, drying, and grinding to obtain the modified hydroxyethyl cellulose.

8. The enhanced alumina ceramic substrate according to claim 7, characterized in that: The mass ratio of the hydroxyethyl cellulose, nano silicon dioxide and silane coupling agent is 1:0.4-0.6:0.2-0.

3.

9. The method for preparing a reinforced alumina ceramic substrate according to claim 1, characterized in that: The steps include: (1) vacuum drying the modified alumina, magnesium oxide and yttrium trioxide respectively; the drying condition is drying at 75-80°C for 10-12 hours; (2) ball-milling the solvent, dispersant, plasticizer, binder and surfactant to obtain a mixed solution, and controlling the pH value of the mixed solution to 8-9 by adding ammonia water; (3) adding the powder obtained by drying in step (1) to the mixed solution obtained in step (2), and continuing ball milling for 30-32 hours; (4) Casting, drying at 95-100°C for 3-4 hours to prepare an alumina ceramic green body, heating to 1600-1650°C and sintering for 5-6 hours to obtain an enhanced alumina ceramic substrate.

10. The method for preparing a reinforced alumina ceramic substrate according to claim 9, characterized in that: In step (3), the ball milling speed is 300-400 r / min, and the ball milling time is 4-5 h.

Citation Information

Patent Citations

  • Novel efficient energy-saving type mortar and preparation method thereof

    CN108264309A

  • Polyurethane material based on modified alumina filler and preparation method thereof

    CN112280289A

  • Alumina-based composite ceramic substrate and preparation method thereof

    CN114656245A

  • Alumina ceramic and production process thereof

    CN115368120A

  • Graphene composite high-thermal-conductivity aluminum substrate, preparation method and application

    CN121536049A

Cited By

  • High-strength wear-resistant multilayer ceramic substrate and preparation method thereof

    CN120554098A